BBC Radio Drama Series Cabin Pressure: Abu Dhabi for Giving Listening Exposure to Students: A View from Humour Perspective - Cendra, Anastasia Nelladia (Indonesian Journal of EFL and Linguistics, 2017)
Using authentic materials to give listening exposure is essential to improve English language learners’ listening skill and using radio is one way to do so. To reduce anxiety in listening, choosing humorous material can be done as humour has been proven beneficial in classroom context, for example, in reducing stress. Using the partial result of a study conducted by the same author and completed by library study about ethics of using humour in the classroom, this study is to investigate whether verbal humour found in BBC Radio Drama Series Cabin Pressure: Abu Dhabi is suitable to be used in classroom context. Analysing every type verbal humour found in the radio drama, this study points out that verbal humour found in BBC Radio Drama Series Cabin Pressure: Abu Dhabi is generally not appropriate to be used in classroom because it has a quite high number of inappropriate verbal humour, such as sarcasm and satire.Keywords: listening exposure, verbal humour, appropriateness.